Respuesta :

Hope it helps! If it is, Brainliest please!
Ver imagen kaikaio

Answer: f(-3) = -4

Concept:

Here, we need to understand the idea of evaluation.  

When encountering questions that gave you an expression with variables, then stated: "If x = a, y = b, z = c" (a, b, c are all constants), this means you should substitute the value given for each variable back to the expression.

Solve:

Given expression

f(n) = 3n + 5

Substitute values into the expression

f(-3) = 3(-3) + 5

Simplify by multiplication

f(-3) = -9 + 5

Simplify by addition

f(-3) = [tex]\boxed{-4}[/tex]

Hope this helps!! :)

Please let me know if you have any questions